Effect of Cyclic Loading on Shear Bond Strength of Orthodontic Brackets: An In Vitro Study - Mohammad Moslem Imani; Farzaneh Aghajani; Nafiseh Momeni; Mohammad Sadegh Ahmad-Akhoundi (Tehran University of Medical Sciences, 2018)
Objectives: In clinical conditions, orthodontic brackets are exposed to periodic stresses mainly induced by mastication and intraoral forces. The objective of the present study was to evaluate the effects of cyclic loading to simulate masticatory forces on shear bond strength (SBS) of metal brackets bonded to teeth using self-etch and total-etch bonding systems. Materials and Methods: Eighty-four caries- and crack-free bovine mandibular incisors were selected and randomly assigned to two groups based on the type of bonding system. After bonding, all samples were thermocycled (500 cycles) followed by cyclic loading of the half of the specimens in each group by applying 40 N load with 2 Hz frequency for 10,000 cycles. The SBS was measured using a universal testing machine. The adhesive remnant index (ARI) score was calculated subsequently. Data were analyzed using Kolmogorov-Smirnov test, two-way ANOVA and Mann-Whitney test. Results: The SBS was 10.09±3.78 MPa and 14.44±6.06 MPa for self-etch and total-etch bonding systems in cyclic loading group, respectively. The SBS was 9.43±5.3 MPa and 11.31±5.42 MPa in self-etch and total-etch groups without cyclic loading, respectively. Cyclic loading did not cause any significant difference in SBS (P>0.05). The ARI scores of the groups were significantly different (P<0.05). Conclusions: The present results demonstrated that low masticatory forces at 10,000 cycles did not have a significant impact on bracket-adhesive SBS; however, they significantly changed the ARI score. Even though the total-etch bonding system yielded higher SBS than the self-etch system, the performance of both was clinically acceptable.